Who or what is to blame for the power paradox in society? - Cornelius, Elma (Stellenbosch Theological Journal, 2021)
We vote for people who seem to be promising good leaders and somehow, they turn out to be terrible leaders. This tendency Keltner (2007) calls the "power paradox". The moment people gain power or success or wealth, their characteristics of empathy, collaboration, open mindedness, fairness, and generosity vanish into thin air and we have to deal with impulsive and self-serving leaders. The experience of power thus damages leaders' social intelligence. The author of this article asks: who or what is to be blamed for this power paradox? Keltner suggests that we need people with a focus on others, who have empathy, a giving personality, gratitude, and unifying stories. The author suggests that spiritual intelligence can fix the power paradox in society as she shows that Keltner's principles for enduring power are no different from the spiritual gifts explained in the Bible of Christianity. Spiritual intelligence is offered as the solution to the power paradox.